Potential cyclodextrin glycosyltransferase producer from locally isolated bacteria - Ramli, Norhayati; Abd. Aziz, Suraini; Hassan, Mohd Ali; Mohammed Alitheen, Noorjahan Banu; Kamaruddin, Kamarulzaman (Academic Journals, 2010)
Cyclodextrin glycosyltransferase (CGTase) is one of the most important groups of microbial amylolytic enzymes that have been used for degradation of starch to yield cyclodextrin (CD) via cyclization reaction. The increasing demand for CD in industrial application has led to an extensive study about CGTase which begin with screening, isolation and characterization of CGTase-producing bacteria. The identification of CGTase producer involves the use of solid media containing phenolphthalein and methyl orange as indicators that was detected by the colour changes. The formations of clearance zone around the bacterial colony in the starch-containing medium were observed and the diameters were measured to gauge the hydrolytic efficiency of the bacteria. Out of 65 soil bacterial samples screened, Bacillus sp. NR5 UPM was identified as the most prolific CGTase producer, which produced highest CGTase activity (11.709 U/ml) and highest b-CD concentration (2.504 mg/ml) with a-CD:b-CD:g-CD ratio was 0.5:91.1:8.4 when using raw soluble starch as a substrate. It also showed as the best CGTase producer when using sago starch as a substrate (15.514 U/ml). This isolate was known as a raw starch-degrading enzyme producer since it has the capability touse raw starch as a substrate. Thus, in the future, this new isolate perhaps can share the biggest market in industrial application.